E-Modul Pembelajaran Mata Kuliah Peminatan Kecerdasan Buatan Program Studi Teknik Informatika IIB Darmajaya Berbasis Android - Puspita Anggun, Meilia; Nur Laila, Siti (Jurnal Etnik: Ekonomi-Teknik, 2023)
The problem of this research is that the modules available in courses specializing in artificial intelligence are still in printed form, so it is necessary to develop learning media to adapt to technological developments that can be used as facilities to facilitate the learning process, especially in material that requires a certain understanding. The purpose of this research is to build an android-based learning e-module application that is more practical and easy to use in the subject of specialization in artificial intelligence, IIB Darmajaya informatics engineering study program. This research method uses Research and Development (R&D) with the ADDIE model development procedure which consists of 6 stages, namely analysis, design, development, implementation, evaluation. The results of this study are an e-module application for learning subjects in the specialization of artificial intelligence which can make it easier for students and lecturers of the IIB Darmajaya informatics engineering study program to carry out learning activities.